Rancang bangun aplikasi pemesanan produksi percetakan berbasis web - Bagas Rizky Perdana; Sharyanto Sharyanto; Iskandar Zulkarnain (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
PT. Lfor Digital Printing is a company that operates in the field of printing or commonly called digital printing. In carrying out the ordering process, this company still does not use computerized applications, so it is considered less efficient and effective because customers still have to come directly to the place to place orders or by telephone or email. That's why a web-based printing production ordering system was created in order to improve the quality of ordering services and also increase customer satisfaction. There are several methods used in making this system, namely the observation method, literature study method, and interview method for data collection methods. The modeling of this system uses the Unifield Modeling Language (UML) method with the PHP and MySQL programming languages ​​for the database.